INTUBATIONS BOWEL IN COMPLEX SURGICAL TREATMENT OF CHILDREN PROLIFERATION PERITONITIS - Ksonz, I.V.; Gritsenko, E.M.; Maksimenko, A.S. (World of Medicine and Biology, 2015)
Distributed peritonitis is a serious and dangerous complication of acute surgical pathology of the abdominal cavity. Among the causes of peritonitis in children, most authors find the most common acute appendicitis, peritonitis hematogenous, acute mesadenitis, inflammation and tumors of the genitals, terminal ileitis, complicated Meckel diverticulum, damage of the abdominal cavity. The researchers considered that the most common cause of distributed peritonitis is acute destructive appendicitis (74-86%).The experience of 60 cases using intubation of the small intestine in acute surgical pathology of abdominal cavity in children.In children operated on peritonitis caused it were: destructive forms of appendicitis (27 cases), postoperative peritonitis, what was going on (8 cases), intra-abdominal abscess (6) inability seams intestinal anastomoses (6), perforation of acute ulcers gut (6) closed abdominal injury with damage to the small intestine (4), appendix stump failure (2), perforation of the small intestine multiple foreign bodies (1). In five cases, children operated on the total peritonitis appendicular abscessed disease for a period of 18 days and the formation of multiple intra-abdominal abscesses.During surgery conducted audit of the abdominal cavity, assessed the nature and amount of fluid, its location, presence and character of fibrin layers, adhesive process, appearance parietal and visceral peritoneum, forming bowel loop abscesses, presence of hemorrhage. Also assessed the state of the intestine, intestinal loops diameter, their color, the thickness of the intestinal wall, preservation or restoration of peristalsis. On the basis of integrated assessment of the extent and nature of the defeat of the abdomen during surgery were determined the modification index of abdominal cavity.The most commonly used transanal intubation (27 cases). Intubation through apendykotsekostom was used in 19 cases nazointestinal 2, intubation through enterostom 8, syhmostom 1 in 3 cases, using a combination of methods. If unable to complete one-stage reorganization of the abdominal cavity in 18 children were perfomed the programmed sanitation relaparotomy.To improve the efficiency of decompression applied through probe enteral therapy, which included conducting postoperative intestinal lavage, Enterosorption, selective intestinal decontamination solutions of antibiotics. Procedures performed 3-4 times a day to restore effective peristalsis, restoration of passage through the intestines, improve the patient under control parameters of endogenous intoxication.A comparison of the dynamics of the postoperative period between groups of children who performed various types of intestinal intubation, significant differences were found. In general, all groups within 3-5 days of the postoperative period there was a steady tendency to decrease endogenous intoxication. Analyzing the results of treatment found that the significant difference in terms of restoration of peristalsis, stool discharge, early enteral nutrition, length of operation of the probe is detected, the duration differed operations in these groups and their stay in hospital. Bowel intubation coupled with through probe enteral therapy is an effective method of eliminating the sources of enterogenic intoxication correction enteric peritonitis widespread failure in children. If you can not complete one-stage rehabilitation is effective abdominal cavity sanation it necessary to perfomed the programmed relaparotomy.Method of bowel intubation has no significant impact on the dynamics of endogenous intoxication and the postoperative period. Choose how intubation determined individually in each case integrated multi intraoperative assessment of the situation.
Keywords: small bowel intubation; diffuses peritonitis; enteral transtube therapy; children